Desenvolvimento de métodos para determinação de metais e metaloides em amostras de sangue animal por DMA e TXRF - Ingrid de Souza Pellegrini (2022)
In this work, the selection of animal blood were performed optimizations and validations of two analytical methods in two instrumental techniques, the Direct Mercury Analyzer (DMA) and the Total Reflection X-Ray Fluorescence Spectrometry (TXRF). The metals determined by TXRF were metals, chromium, metals and selenium. The parameters of linear quantification, estimation in the validation by DMA were obtained by DMA, repeatability, precision, precision, and robustness. The parameters were the same for validation by TXRF, except for linearity. The LQ for mercury was 0.054 ng. As for arsenic, the LQ was 0.51 µg/L, for chromium 1.03 µg/L, elaborated 0.68 µg/L and selenium 0.32 µg/L. For all metals cited, such as medium recoveries and for precision that satisfy the 80% to 120% durability range. The precision of the methods was obtained from the results of repeatability and precision obtained. Regarding the only robust change change, change for atomization time change. For arsenic, the changes made in the times between preparation and drying reading were significant. For chromium, there was no significant change. o Time and selenium, only the time between sample preparation and reading was significant.